Foreign Body Response to Subcutaneous Implants in Diabetic Rats - Socarrás, Teresa Oviedo; Vasconcelos, Anilton C.; Campos, Paula P.; Pereira, Nubia B.; Souza, Jessica P. C.; Andrade, Silvia P. (PloS one, 2014)
Implantation of synthetic matrices and biomedical devices in diabetic individuals has become a common procedure to repair and/or replace biological tissues. However, an adverse foreign body reaction that invariably occurs adjacent to implant devices impairing their function is poorly characterized in the diabetic environment. We investigated the influence of this condition on the abnormal tissue healing response in implants placed subcutaneously in normoglycemic and streptozotocin-induced diabetes in rats. In polyether-polyurethane sponge discs removed 10 days after implantation, the components of the fibrovascular tissue (angiogenesis, inflammation, fibrogenesis, and apoptosis) were assessed. Intra-implant levels of hemoglobin and vascular endothelial growth factor were not different after diabetes when compared with normoglycemic counterparts. However, there were a lower number of vessels in the fibrovascular tissue from diabetic rats when compared with vessel numbers in implants from non-diabetic animals. Overall, the inflammatory parameters (neutrophil accumulation--myeloperoxidase activity, tumor necrosis factor alpha, and monocyte chemotactic protein-1 levels and mast cell counting) increased in subcutaneous implants after diabetes induction. However, macrophage activation (N-acetyl-β-D-glucosaminidase activity) was lower in implants from diabetic rats when compared with those from normoglycemic animals. All fibrogenic markers (transforming growth factor beta 1 levels, collagen deposition, fibrous capsule thickness, and foreign body giant cells) decreased after diabetes, whereas apoptosis (TUNEL) increased. Our results showing that hyperglycemia down regulates the main features of the foreign body reaction induced by subcutaneous implants in rats may be relevant in understanding biomaterial integration and performance in diabetes.